Cooperative learning in physical education : a research-based approach - Dyson, Ben.; Casey, Ashley (Abingdon, Oxon : Routledge, 2012)
'Cooperative Learning is a dynamic instructional model that can teach diverse content to students at different grade levels, with students working together in small, structured, heterogeneous groups to master subject content. It has a strong research tradition, is used frequently as a professional development tool in general education and is now emerging in physical education. This book defines Cooperative Learning in physical education and examines how to implement Cooperative Learning in a variety of educational settings. It explores Cooperative Learning in physical education from three main perspectives. The first, context of learning, provides descriptions of Cooperative Learning in different levels of education (elementary school, secondary school, and university physical education). The second, Cooperative Learning in the curriculum, offers case studies from teachers and researchers of their experiences of implementing Cooperative Learning within their own national context. The third perspective, key aspects of Cooperative Learning, examines how the different elements of the model have been foregrounded in efforts to enhance learning in physical education. As the only text to provide international perspectives, from eight different countries, of Cooperative Learning in physical education, this book is important reading for any student, researcher or teacher with an interest in physical education, sport education, sport pedagogy, curriculum development or methods for learning and teaching'--
Includes bibliographical references and index.
Keywords: Physical education and training -- Study and teaching; Group work in education -- United States